Bluey. Mini Bluey (Bluey series., 2024)
"When Dad complains about how different Bluey and Bingo are, Bluey decides to color Bingo to be more like her. But when Bluey paints herself to look more like her little sister, Mum and Dad like Big Bingo more! Will Bluey and Bingo learn to be happy just how they are?" --